The Effect of Stress Distribution on Tibial Implants with a Honeycomb Structure in Open-Wedge High Tibial Osteotomy - Zengbo Xu; Chunhui Mu; Yi Xia (Applied Sciences)
A tibial implant is necessary to provide mechanical support in open-wedge high tibial osteotomy (OWHTO) treatment of knee osteoarthritis. The pore structure and porosity of implants exert significant effect on tibia stress distribution and lower limb alignment stability. In this study, finite element (FE) analysis and in vitro biomechanical experiments were utilized to evaluate the impact of different tibial implants on postoperative tibial stress distribution. The biomechanical experimental results of experiments on tibial implants exhibit similar mechanical response patterns to the established finite element model, whose maximum displacement error is 1.18% under 1500 N compressive load. The hybrid porous implant developed in this study demonstrated significant stress reductions in both tibial bone (19.97% and 15.33% lower than mono-porous configurations at 73% porosity) and implant body (31.60% and 11.83% reductions, respectively), while exhibiting diminished micromotion tendencies. This consistent performance pattern was maintained across the entire porosity spectrum (53–83%) in implanted specimens. In summary, the finite element model established using authentic tibial CT data can effectively guide the structural design of tibial implants, and optimized pore structure design can provide enhanced mechanical support effects for tibial implants.